Simulated productivity of conceptual, multi-headed tree planting devices - Ersson, Back Tomas; Jundén, Linus; Lindh, Erik Mattias; Bergsten, Urban (2014)
Mechanized tree planting is presently enjoying a revival in Fennoscandia with increased focus on further technical development. To explore the productivity effect of multiple heads on crane-mounted tree planting devices, we used a discrete-event simulation tool in which excavator-mounted one- to four-headed devices reforested clearcuts with variable frequencies of obstacles. During the simulations, the device models either mounded or inverted soil and then planted seedlings. A planting head could be hindered by stones and roots from performing these tasks, thus causing queuing delays for multi-headed devices. Surface boulders, stumps, and humus layers also slowed down the work. The results showed that productivity increased significantly with increasing numbers of planting heads on terrain with sparse or moderate obstacles, regardless of using faster or slower soil preparation methods or seedling reloading systems. However, on obstacle-rich terrain, three-headed planting devices were more productive than four-headed, while one-headed were as equally productive as twoheaded devices. Obstacle-rich terrain sometimes inhibited those large four-headed devices from planting even one seedling at a given machine stationary point. Therefore, we conclude that three planting heads per cranemounted device seems to be the most realistic configuration for combining high productivity with good silvicultural results on all the terrain types that a planting machine might work on in Fennoscandia. Future studies should investigate the silvicultural effects of different tree spacing geometries and the corresponding suitable geometrical design of three-headed crane-mounted planting devices.